2003
DOI: 10.1161/01.str.0000071109.23410.ab
|View full text |Cite
|
Sign up to set email alerts
|

Low Vitamin B6 but Not Homocyst(e)ine Is Associated With Increased Risk of Stroke and Transient Ischemic Attack in the Era of Folic Acid Grain Fortification

Abstract: Low B6 but not tHcy was strongly associated with cerebrovascular disease in this postfortification, folate-replete sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 10 publications
2
65
2
1
Order By: Relevance
“…A strong association between stroke/TIA and low PLP (defined as levels less than 20 nmol/l) was independent of other well-established vascular risk factors, including total plasma homocysteine concentrations. Furthermore, results from that study identified a possible protective effect for higher PLP concentrations (29) . In the context of the Health Professional Follow-up Study, He et al evaluated dietary intakes of vitamin B 6 together with the intake of other B vitamins by a semiquantitative FFQ (51) in relation to the risk of ischaemic and haemorrhagic stroke (52) .…”
Section: Vitamin B 6 and Strokementioning
confidence: 85%
“…A strong association between stroke/TIA and low PLP (defined as levels less than 20 nmol/l) was independent of other well-established vascular risk factors, including total plasma homocysteine concentrations. Furthermore, results from that study identified a possible protective effect for higher PLP concentrations (29) . In the context of the Health Professional Follow-up Study, He et al evaluated dietary intakes of vitamin B 6 together with the intake of other B vitamins by a semiquantitative FFQ (51) in relation to the risk of ischaemic and haemorrhagic stroke (52) .…”
Section: Vitamin B 6 and Strokementioning
confidence: 85%
“…Our study does not support the hypothesis that vitamin B-6 deficiency impairs PE methylation by altering hepatic SAM and SAH contents. Strong epidemiological associations exist between low vitamin B-6 status and risk of cardiovascular disease, other forms of vascular disease, and stroke (22,33,34,44), although the mechanism is unclear. Epidemiological studies also show associations between low plasma PLP concentration and markers of inflammation (30,31,43).…”
Section: Discussionmentioning
confidence: 99%
“…In one study high-dose vitamin B 6 therapy was reported to be effective in reducing cardiovascular events in patients with elevated homocysteine levels due to cystathionine B synthase abnormalities; 53 however, such treatment was not effective in reducing elevated homocysteine levels in adults with mild elevations in homocysteine. 54 In a recent case-control study, Kelly and associates 55 found a significantly strong independent association between low levels of vitamin B 6 and stroke or transient ischemic attack but not between elevated homocysteine levels and vascular events.…”
Section: B Vitaminsmentioning
confidence: 97%